Impact of elemental iron on human spermatozoa and mouse embryonic development in vitro in a defined synthetic protein-free culture system / Safaa Mahmoud Naes - Safaa, Mahmoud Naes (2018)
The element iron is essential for life and plays a number of key roles in biological processes and it is involved in cell development, some of which are intimately related to spermatogenesis and spermatozoa metabolism. Iron and its compounds within certain limits are not fundamentally toxic for the human organisms. However, the role of iron in infertility has not been widely investigated. Infertility, which known as a failure to achieve conception after one year of regular unprotected sexual intercourse, affects 10– 15% of couples and approximately 80 million couples worldwide. The common causes of infertility include male factors, female factors, and unexplained causes. The rate of male factors is 30% to 40%, female factors 40%, and unexplained causes 10% of infertility cases. This study aims to ascertain the optimal level of iron needed for optimal embryonic development (Spermatozoa and embryos) in protein free culture media, and toxic levels to enable its application in assisted reproductive technologies to help increase the pregnancy rates. Different levels of ferric iron concentrations were prepared using HEPES and protein- free culture media. The levels of ferric iron investigated closely resembled the normal range for human plasma iron (0.6-1.7 µg/ml). These levels were investigated to determine the optimal and tolerance levels of iron for human spermatozoa. Ferric chloride was used as source of iron in the HEPES-buffered synthetic protein-free medium. Normozoospermic semen samples (n=24) were incubated with different concentrations of iron (0.5, 1, 1.5, 2, 4, 8, 12, and 16 µg/ml) in HEPES buffered protein-free culture medium at room temperature for 1hr and 20hrs. Motility and vitality of spermatozoa were measured according to WHO Manual 2010. Spermatozoa activity and sperm DNA integrity were evaluated at room temperature at 1hr and 20hrs. 2.0 µg/ml (35.8 µM) of ferric iron was the optimal level of ferric iron iv with range of tolerance levels (0.5- 2 µg/ml) which appeared beneficial for spermatozoa motility at 1hr and up to 20hrs. Levels above 4.0 µg/ml were toxic to human spermatozoa. Days 1-4 Quakenbush Special (Qs) mouse embryos were recovered (n=954) from stimulated females, pooled and randomly apportioned for individual treatments of different concentrations of ferric chloride (2, 5, 10, 20 and 50 µM for tolerance study and 100, 200, 300, 400 and 500 µM/L for toxicity study). The investigation on iron toxicity utilized 206 day 2 Qs mouse embryos. Medium supplemented with iron (2 to 50 µM/L of ferric chloride) had higher percentage of blastocysts than control in all treatments. In contrast, the percentages of blastocysts were lower than control in another experiment performed to investigate iron toxicity which contained 100 to 500 µM/L. This study found that ferric iron at physiological levels of human plasma appears to enhance spermatozoa motility, preserve its DNA integrity and may increase percentage of blastocysts developed and embryo development because of its critical role in cell proliferation. However, increasing the concentrations of ferric iron above the physiological levels had harmful effects on spermatozoa motility, sperm DNA integrity and blastocysts development.